The effect of L-Tryptophan on hemorrhagic shock induced bacterial translocation - Bülbüller, N; Pektas, B; Özdarendeli, A; Dogru, O; Aygen, E; Akpolat, N (Academic Press Inc Elsevier Science, 2005)
Hemorrhagic shock causes mucosal damage in intestine and it results in translocation of bacteria to distant organs. In this study, effects of various doses of L-Tryptophan on the prevention of bacterial translocation in hemorrhagic shock induced rabbits were investigated. This study was carried out on six groups, each was consisting of 10 rabbits. While any procedure was conducted on the rabbits in group 1 (as a control group), 1 x 10(10) Escherichia coli isolate were administered rabbits in the other groups by gavage. In groups 3, 4, 5, and 6, hemorrhagic shock was induced. After induction of hemorrhagic shock, 10, 50, and 200 mg/kg L-Tryptophan were intragastrically administered to animals in groups 4, 5, and 6, respectively. Blood and terminal ileum samples were taken to detect bacterial translocation by polymerase chain reaction and mucosal damage by histopathological examination at 24 h after hemorrhagic shock. The occurrence of bacterial translocation increased as well when intestinal bacterial intensity was increased (P < 0.05). The most intensive bacterial translocation was formed in group 3 as a result of the additive effect of hemorrhagic shock to bacterial augmentation. It was observed that bacterial translocation was significantly reduced in groups 5 and 6 that are 50 and 200 mg/kg L-Tryptophan were administered (P < 0.01). Histopathological changes on mucosa and submucosa support these results. As a result, we concluded that augmentation of intestinal bacterial intensity induces bacterial translocation, the addition of hemorrhagic shock to bacterial augmentation makes more excessive translocation and mucosal changes have effective roles in these events. L-Tryptophan decreased the intestinal mucosal damage and bacterial translocation induced by hemorrhagic shock, in a dose-dependent manner. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: hemorrhagic shock; bacterial translocation; L-Tryptophan; melatonin; polymerase chain reaction